2020
DOI: 10.3389/fphys.2020.00518
|View full text |Cite
|
Sign up to set email alerts
|

Disparate Effects of Diabetes and Hyperlipidemia on Experimental Kidney Disease

Abstract: It is well established that diabetes is the major cause of chronic kidney disease worldwide. Both hyperglycemia, and more recently, advanced glycation endproducts, have been shown to play critical roles in the development of kidney disease. Moreover, the renin-angiotensin system along with growth factors and cytokines have also been shown to contribute to the onset and progression of diabetic kidney disease; however, the role of lipids in this context is poorly characterized. The current study aimed to compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…20 Hyperlipidemia has been implicated in the pathogenesis of DKD, however experimental models show that elevated levels of total cholesterol and triglycerides were not sufficient to drive overt changes in renal structure and function. 37 On the contrary, prospective cohort study of type-2 DM patients for a median period of 5.8 years showed that elevated total cholesterol levels were associated with increased risk for the development of both moderate and severe increase in the UACR. 15 Similarly, Samsu 38 reported in a review that low levels of total cholesterol and triglycerides were associated with regression from moderate albuminuria to normal UACR.…”
Section: Discussionmentioning
confidence: 98%
“…20 Hyperlipidemia has been implicated in the pathogenesis of DKD, however experimental models show that elevated levels of total cholesterol and triglycerides were not sufficient to drive overt changes in renal structure and function. 37 On the contrary, prospective cohort study of type-2 DM patients for a median period of 5.8 years showed that elevated total cholesterol levels were associated with increased risk for the development of both moderate and severe increase in the UACR. 15 Similarly, Samsu 38 reported in a review that low levels of total cholesterol and triglycerides were associated with regression from moderate albuminuria to normal UACR.…”
Section: Discussionmentioning
confidence: 98%
“…Dyslipidemia is found in most patients with CKD, even in the early stages and is related to the decline in renal function [ 40 , 41 ]. Previous data demonstrated that hyperlipidemia was slightly associated with renal pathology and that the increase in plasma lipids alone was not sufficient to cause significant renal damage [ 42 ]. It was also reported that the more severe the diabetes, the more severe the renal dysfunction [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous data demonstrated that hyperlipidemia was slightly associated with renal pathology and that the increase in plasma lipids alone was not sufficient to cause significant renal damage [ 42 ]. It was also reported that the more severe the diabetes, the more severe the renal dysfunction [ 42 ]. In fact, hyperglycemia is associated with CKD development [ 43 ], which can promote changes in renal function [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Ang II-based activation of AT1R causes insulin resistance by increasing hepatic triglyceride levels, which is thought to contribute to the development of diabetes [28,43]. Diabetic dyslipidemia is associated with damage to vital organs such as the heart and kidneys [44,45]. Local RAAS in the kidneys has been evidenced, in various studies, to cause morphological changes that affect kidney function [44,46].…”
Section: Local Raas and T2dmentioning
confidence: 99%
“…Diabetic dyslipidemia is associated with damage to vital organs such as the heart and kidneys [44,45]. Local RAAS in the kidneys has been evidenced, in various studies, to cause morphological changes that affect kidney function [44,46]. In T2D, systemic and kidney RAAS have been positively correlated with proteinuria and hypertension [46,47].…”
Section: Local Raas and T2dmentioning
confidence: 99%